2024
DOI: 10.1109/access.2024.3353195
|View full text |Cite
|
Sign up to set email alerts
|

Artifact Reduction in 3D and 4D Cone-Beam Computed Tomography Images With Deep Learning: A Review

Mohammadreza Amirian,
Daniel Barco,
Ivo Herzig
et al.

Abstract: Deep learning based approaches have been used to improve image quality in cone-beam computed tomography (CBCT), a medical imaging technique often used in applications such as imageguided radiation therapy, implant dentistry or orthopaedics. In particular, while deep learning methods have been applied to reduce various types of CBCT image artifacts arising from motion, metal objects, or lowdose acquisition, a comprehensive review summarizing the successes and shortcomings of these approaches, with a primary foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 135 publications
0
1
0
Order By: Relevance
“…However, these images still contain artifacts (Schulze et al 2011 ) that compromise the fidelity of the ‘ground truth’, leading to potential inaccuracies in quantitative analysis. As an alternative, techniques such as iterative reconstructions (Sun et al 2015 ) and DL-based methods (Bayaraa et al 2020 , Amirian et al 2024 ) have shown capabilities in enhancing CBCT quality and reducing artifacts, which can potentially be used to reconstruct the CBCTs to serve as the ‘ground truth’, if the raw x-ray projections are available.…”
Section: Discussionmentioning
confidence: 99%
“…However, these images still contain artifacts (Schulze et al 2011 ) that compromise the fidelity of the ‘ground truth’, leading to potential inaccuracies in quantitative analysis. As an alternative, techniques such as iterative reconstructions (Sun et al 2015 ) and DL-based methods (Bayaraa et al 2020 , Amirian et al 2024 ) have shown capabilities in enhancing CBCT quality and reducing artifacts, which can potentially be used to reconstruct the CBCTs to serve as the ‘ground truth’, if the raw x-ray projections are available.…”
Section: Discussionmentioning
confidence: 99%